Method for producing cathode active material having spinel structure
By combining the mixed metal composition with water, nickel and manganese salts, a cathode active material with spinel structure is formed, which solves the problems of waste lithium-ion battery resource recycling and battery performance, and achieves efficient battery reuse and performance promote.
Patent Information
- Application Number
- CN202380038407.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-05
- Filing Date
- 2023-04-20
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to effectively recycle and reuse cathode active materials in waste lithium-ion batteries, resulting in waste of resources and poor battery performance.
By contacting the mixed metal composition with water to form a solution, adding nickel salt and manganese salt, forming a precipitate in combination with an alkaline solution, and forming a cathode active material with a spinel structure in the heat treatment, the battery performance is improved using the recycled raw materials.
It realizes the extraction of cathode active materials with spinel structure from waste lithium-ion batteries, improves the discharge capacity and cycle stability of the battery, and reduces production costs and resource waste.
Smart Images

Figure CN119137073A_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 338,485 filed in the U.S. Patent and Trademark Office on May 5, 2022, and all benefits arising therefrom under 35 U.S.C. §119, the contents of which are incorporated herein by reference in their entirety. Background Art
[0003] Lithium-ion batteries have become a popular power source in a variety of applications including consumer electronics and electric vehicles. Millions of batteries have been produced. Nevertheless, there is a continuing need for improved methods for recycling and reusing spent batteries. It would be particularly advantageous to provide methods for preparing cathode active materials with specific structures for new batteries from in addition to new raw materials. Summary of the invention
[0004] In one aspect, a method for making a cathode active material includes contacting a mixed metal composition with water to form a first solution, the mixed metal composition comprising nickel and greater than 0 to 2 weight percent of a compound containing Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed metal composition; adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution; adding a co-solvent to the second solution to provide a third solution; combining the third solution and an alkaline solution to form a precipitate; adding a lithium compound to the precipitate to form a mixture; and heat treating the mixture under conditions effective to provide a cathode active material, wherein the cathode active material comprises at least one phase having a spinel structure.
[0005] In one aspect, a method for making a cathode active material includes contacting a mixed metal composition with water to form a first solution, the mixed metal composition including nickel and manganese and greater than 0 to 2 weight percent of a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed metal composition; adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution; adding a co-solvent to the second solution to provide a third solution; combining the third solution and an alkaline solution to form a precipitate; adding a lithium compound to the precipitate to form a mixture; and heat treating the mixture under conditions effective to provide a cathode active material, wherein the cathode active material comprises at least one phase having a spinel structure.
[0006] In one aspect, a method for making a cathode active material includes contacting a mixed metal composition with water to form a first solution, the mixed metal composition comprising manganese and greater than 0 to 2 weight percent of a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed metal composition; adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution; adding a co-solvent to the second solution to provide a third solution; combining the third solution and an alkaline solution to form a precipitate; adding a lithium compound to the precipitate to form a mixture; and heat treating the mixture under conditions effective to provide a cathode active material, wherein the cathode active material comprises at least one phase having a spinel structure.
[0007] In one aspect, the cathode active material comprises a material having the formula Li 1+x M 2+y O 4-z A z and a first phase having a spinel structure; and a second phase, wherein M is Ni and Mn; A is oxygen vacancy, F, Cl, or a combination thereof; 0≤x≤0.2; 0≤y≤0.1; 0≤z≤0.1; and the second phase is derived from recycled raw materials.
[0008] In one aspect, the cathode active material comprises a material having the formula Li 1+x M 2+y O 4-z A z And a first phase having a spinel structure, wherein M is Ni and Mn, A is oxygen vacancy, F, Cl, or a combination thereof, 0≤x≤0.2, 0≤y≤0.1, 0≤z≤0.1, and wherein the first phase further contains Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof.
[0009] The above described and other features are exemplified by the following figures and detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] The following figures illustrate exemplary embodiments.
[0011] Figure 1 A flow chart of an exemplary method according to the present disclosure is shown. DETAILED DESCRIPTION
[0012] The inventors have discovered methods for remanufacturing batteries and battery materials, particularly cathode active materials and precursors thereof, wherein the cathode active materials have at least one phase having a spinel structure. Despite utilizing a high proportion of feedstock derived from spent batteries or battery manufacturing waste, cathode active materials prepared according to the methods described herein are expected to exhibit comparable or improved battery performance.
[0013] Thus, one aspect of the present disclosure is a method of making a cathode active material from a mixed metal composition. In one aspect, the mixed metal composition comprises a mixed metal sulfate, a mixed metal nitrate, a mixed metal carbonate, a mixed metal halide, a mixed metal hydroxide, a mixed metal oxalate, or a combination thereof. In a specific aspect, the mixed metal composition comprises a mixed metal sulfate.
[0014] In one aspect, the mixed metal composition comprises nickel. Based on the total weight of the mixed metal composition, the nickel may be present in the mixed metal composition in an amount of at least 5 weight percent, or at least 10 weight percent, or at least 15 weight percent, or at least 18 weight percent. In one aspect, based on the total weight of the mixed metal composition, the nickel may be present in the mixed metal composition in an amount of 5 to 98 weight percent, or 5 to 85 weight percent, or 5 to 75 weight percent, or 5 to 50 weight percent, or 15 to 25 weight percent. Based on the total weight of the mixed metal composition, the mixed metal composition may further comprise a compound containing Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof in an amount greater than 0 to 2 weight percent. For example, the mixed metal composition can include greater than 0 to 1.5 weight percent, or greater than 0.0001 to 1 weight percent, or greater than 0.001 to 0.5 weight percent, or greater than 0 to 0.1 weight percent, or greater than 0 to 0.01 weight percent (100 ppm) of a compound containing Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed metal composition. In one aspect, the mixed metal composition can include greater than 0 to 1000 ppm, or greater than 0 to 750 ppm, or 5 to 750 ppm, or 5 to 1000 ppm, or 25 to 1000 ppm, or 25 to 750 ppm, or 50 to 750 ppm, or 100 to 750 ppm of a compound containing Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed metal composition. For example, the mixed metal composition can include 0.5 to 1.5 weight percent Co, 50 to 300 ppm Cu, 50 to 200 ppm Al, 5 to 100 ppm Fe, and 5 to 100 ppm F, each based on the total weight of the mixed metal composition. In one aspect, the mixed metal composition can include lithium. When present, lithium can preferably be present in the mixed metal composition in an amount of 100 to 1000 ppm, based on the total weight of the mixed metal composition.
[0015] In one aspect, the mixed metal composition comprises nickel and manganese (e.g., wherein nickel and manganese are present in the mixed metal composition as major components). For example, nickel and manganese may be present in the mixed metal composition in an amount of at least 5 weight percent, or at least 10 weight percent, or at least 15 weight percent, or at least 18 weight percent, based on the total weight of the mixed metal composition. In one aspect, nickel and manganese may be present in the mixed metal composition in an amount of 5 to 98 weight percent, or 5 to 85 weight percent, or 5 to 75 weight percent, or 5 to 50 weight percent, or 15 to 25 weight percent, based on the total weight of the mixed metal composition. The mixed metal composition may further comprise greater than 0 to 2 weight percent of a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed metal composition. For example, the mixed-metal composition can include greater than 0 to 1.5 weight percent, or greater than 0.0001 to 1 weight percent, or greater than 0.001 to 0.5 weight percent, or greater than 0 to 0.1 weight percent, or greater than 0 to 0.01 weight percent (100 ppm) of a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed-metal composition. In one aspect, the mixed-metal composition can include greater than 0 to 1000 ppm, or greater than 0 to 750 ppm, or 5 to 750 ppm, or 5 to 1000 ppm, or 25 to 1000 ppm, or 25 to 750 ppm, or 50 to 750 ppm, or 100 to 750 ppm of a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed-metal composition. For example, the mixed metal composition can include 0.5 to 1.5 weight percent Co, 50 to 300 ppm Cu, 50 to 200 ppm Al, 5 to 100 ppm Fe, and 5 to 100 ppm F, each based on the total weight of the mixed metal composition. In one aspect, the mixed metal composition can include lithium. When present, lithium can preferably be present in the mixed metal composition in an amount of 100 to 1000 ppm, based on the total weight of the mixed metal composition.
[0016] In one aspect, the mixed metal composition comprises manganese. Based on the gross weight of the mixed metal composition, manganese may be present in the mixed metal composition in an amount of at least 5 weight percent, or at least 10 weight percent, or at least 15 weight percent, or at least 18 weight percent. In one aspect, based on the gross weight of the mixed metal composition, manganese may be present in the mixed metal composition in an amount of 5 to 98 weight percent, or 5 to 85 weight percent, or 5 to 75 weight percent, or 5 to 50 weight percent, or 15 to 25 weight percent. Based on the gross weight of the mixed metal composition, the mixed metal composition may further comprise a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, in an amount greater than 0 to 2 weight percent. For example, the mixed-metal composition can include greater than 0 to 1.5 weight percent, or greater than 0.0001 to 1 weight percent, or greater than 0.001 to 0.5 weight percent, or greater than 0 to 0.1 weight percent, or greater than 0 to 0.01 weight percent (100 ppm) of a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed-metal composition. In one aspect, the mixed-metal composition can include greater than 0 to 1000 ppm, or greater than 0 to 750 ppm, or 5 to 750 ppm, or 5 to 1000 ppm, or 25 to 1000 ppm, or 25 to 750 ppm, or 50 to 750 ppm, or 100 to 750 ppm of a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed-metal composition. For example, the mixed metal composition may include 0.5 to 1.5 weight percent Co, 50 to 300 ppm Cu, 50 to 200 ppm Al, 5 to 100 ppm Fe, and 5 to 100 ppm F, each based on the total weight of the mixed metal composition. In one aspect, the mixed metal composition may further include lithium. In one aspect, lithium may preferably be present in the mixed metal composition in an amount of 100 to 1000 ppm, based on the total weight of the mixed metal composition.
[0017] In one aspect, the mixed metal composition can include nickel and greater than 0 to 2 weight percent of Co, Al, Cu, Fe, Mg, F, Si, or a combination thereof, based on the total weight of the mixed metal composition. In one aspect, the mixed metal composition can include nickel and manganese and greater than 0 to 2 weight percent of Co, Al, Cu, Fe, Mg, F, Si, or a combination thereof, based on the total weight of the mixed metal composition. In one aspect, the mixed metal composition can include manganese and greater than 0 to 2 weight percent of Co, Al, Cu, Fe, Mg, F, Si, or a combination thereof, based on the total weight of the mixed metal composition.
[0018] The mixed metal composition can be obtained, for example, from depleted lithium ion batteries, lithium ion battery production waste, etc., or a combination thereof. For example, the mixed metal composition can be obtained from recycled raw materials, preferably from post-industrial recycled raw materials, post-consumer recycled raw materials, or a combination thereof. In one aspect, Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof in a compound comprising Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof is produced from recycled raw materials (e.g., depleted batteries or battery manufacturing waste). Depleted lithium ion batteries (or any of the above lithium ion battery component sources) can be crushed, granulated, shredded, etc., and a physical separation process is performed to separate solid battery components (e.g., housing, electrodes, tabs, headers, fuses, etc.) from volatile components (e.g., electrolyte solvents). The electrolyte salt (e.g., LiPF6) can be removed by soaking in a suitable solvent (e.g., propylene carbonate), and the remaining undissolved materials (e.g., electrode materials, current collectors) can be separated, for example, by filtration. The electrode particles can be separated from the residual current collector material, for example, by contacting with a solvent suitable for dissolving the electrode particles or by dissolving the binder to release the electrode particles, to facilitate the removal of the solid metal conductor component. The separated electrode particles can be contacted with a leaching solution to extract elements such as Ni, Co, Mn, Al, Li, and Fe. Exemplary leaching solutions may include, but are not limited to, sulfuric acid (e.g., 2 to 5 molar (M) sulfuric acid), optionally including hydrogen peroxide. The resulting solution can be centrifuged or filtered to remove any particles, and the resulting solution is subjected to conditions effective to induce crystallization or precipitation of the desired mixed metal composition. For example, the filtered solution can be concentrated (e.g., in an evaporator) at 75 to 85°C, or 78 to 82°C, or 80°C. The concentrated solution can be cooled to a temperature, for example, below 20°C, or 10 to 18°C, or 15°C, to crystallize the mixed metal composition.
[0019] The precipitated or recrystallized mixed metal composition can be separated, for example, using any suitable solid-liquid separation technique, such as filtration, centrifugation, or a combination thereof. In one aspect, the mixed metal composition is dehydrated to a moisture content of 10% or less (e.g., 1 to 10% or 5 to 10%) based on the total weight of the mixed metal composition product.
[0020] The mixed metal composition can be contacted with water to form a first solution. The first solution can have a pH that is effective to dissolve the mixed metal composition, which can be selected by a skilled artisan without undue experimentation. In one aspect, the first solution can have a pH of less than 7, such as less than 6.5. For example, when the mixed metal composition comprises a mixed metal hydroxide, an acidic pH can be preferred to ensure dissolution of the mixed metal hydroxide.
[0021] The method further comprises adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution. In one aspect, the salt can be a virgin material (i.e., not recovered or recycled from a depleted lithium-ion battery, or not previously used). In one aspect, the nickel salt, the manganese salt, or a combination thereof is a sulfate or hydroxide thereof (e.g., nickel sulfate, manganese sulfate, nickel hydroxide, manganese hydroxide, or a combination thereof). In one aspect, the salt comprises NiSO4 and MnSO4. The use of hydrates of NiSO4 and MnSO4 is mentioned.
[0022] An amount of salt may be added to effectively obtain the desired stoichiometric nickel and manganese. For example, a nickel salt, a manganese salt, or a combination thereof may be added to the first solution in an amount effective to provide a molar ratio of Ni:Mn of greater than 0 to 0.5:greater than 0 to 2, such as 0.5:1.5.
[0023] The mixed metal composition of the first solution (e.g., recovered or recycled from a depleted lithium-ion battery or manufacturing waste) can be contacted with a virgin salt in an appropriate amount to provide a stoichiometrically adjusted mixed metal composition. In one aspect, the mixed metal composition (i.e., of the first solution) can account for 10 to 95 weight percent of the stoichiometrically adjusted mixed metal composition of the second solution. Within this range, the mixed metal composition can account for 15 to 95 weight percent, or 20 to 95 weight percent, or 25 to 95 weight percent, or 30 to 90 weight percent of the stoichiometrically adjusted mixed metal composition based on the total weight of the second solution.
[0024] The second solution may have a pH that is the same as or different from the pH of the first solution. In one aspect, the pH of the second solution may be less than 7, or less than 6.5. As described above, salt is added to obtain a mixed metal composition of nickel, manganese, or a combination thereof of the desired stoichiometry of the second solution.
[0025] In addition to the stoichiometrically adjusted mixed metal composition, the second solution may further include 0.0001 to 2 weight percent Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the stoichiometrically adjusted mixed metal composition, or 0.0001 to 2 weight percent Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the stoichiometrically adjusted mixed metal composition. In other words, the above-mentioned additional components of the mixed metal composition (e.g., Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof) are not removed and therefore remain in the second solution. In one aspect, these components are neither added to the first solution nor to the second solution. Instead, in one aspect, these components are present at the beginning of the method and are derived from the mixed metal feedstock used in the disclosed method, such as from recycled batteries or battery waste.
[0026] The method further includes adding a co-solvent to the second solution to provide a third solution. The co-solvent is miscible with water and does not cause precipitation of the mixed metal composition. Exemplary co-solvents may include, for example, C 1-8 Alcohol, C 1-8 Alkylene glycol, C 1-8 Alkylene triols, or combinations thereof. In one aspect, the co-solvent can include ethanol, isopropanol, ethylene glycol, diethylene glycol, or combinations thereof.
[0027] The co-solvent may be added to the second solution such that the third solution contains the co-solvent in an amount of 1 to 50 weight percent, preferably 5 to 15 weight percent, based on the total weight of the third solution.
[0028] The third solution may have a pH that is the same or different from the pH of the first solution. In one aspect, the pH of the third solution may be less than 7, or less than 6.5. The use of a third solution having a pH of 4 to 6.5, or 4.5 to 6 is mentioned.
[0029] In addition to the stoichiometrically adjusted mixed metal composition, water and co-solvent, the third solution may further contain, based on the total weight of the stoichiometrically adjusted mixed metal composition, 0.0001 to 2 weight percent Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, or based on the total weight of the stoichiometrically adjusted mixed metal composition, 0.0001 to 2 weight percent Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof. In other words, the above components of the mixed metal composition (e.g., Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof) are not removed and therefore remain in the third solution. It should be noted that these components are not added to any of the first solution, the second solution, and the third solution. Instead, they are present at the beginning of the method, originating from the mixed metal feedstock used in the disclosed method, such as from recycled batteries or battery waste.
[0030] The method further comprises combining the third solution with the alkaline solution to form a precipitate. In one aspect, the alkaline solution can be added to the third solution. In one aspect, the third solution is preferably added to the alkaline solution to form a precipitate.
[0031] The alkaline solution is preferably an alkaline aqueous solution, and thus may contain a suitable base in water. The base may include, for example, an alkali metal hydroxide, ammonia, an alkali metal carbonate, an alkali metal bicarbonate, or a combination thereof. The combination of the alkaline solution and the third solution may be accompanied by stirring, for example at a temperature of 25 to 90° C. at a speed of 500-1500 RPM.
[0032] In one aspect, the alkaline solution can comprise an alkali carbonate, an alkali bicarbonate, or a combination thereof. In one aspect, when used in combination, the alkali carbonate and the alkali bicarbonate can be present in a molar ratio of 1.04:1 to 1:1.04, preferably 1.01:1 to 1:1.01. In a specific aspect, the molar ratio of the alkali carbonate to the alkali bicarbonate can be 1:1. When the alkaline solution comprises an alkali carbonate, an alkali bicarbonate, or a combination thereof, the alkaline solution can be combined with the third solution in an amount effective to provide a pH greater than 7, preferably 7 to 10, or 7 to 9, or 7 to 8.
[0033] In one aspect, the alkaline solution may comprise an alkali metal hydroxide and optional ammonia. In one aspect, the alkaline solution may comprise an alkali metal hydroxide and ammonia, and the molar ratio of the alkali metal hydroxide to the ammonia may be, for example, 2:1 to 1:2, 3:2 to 2:3, 1.04:1 to 1:1.04, preferably 1.01:1 to 1:1.01. In a particular aspect, the molar ratio of the alkali metal hydroxide to the ammonia may be 1:1. When the alkaline solution comprises an alkali metal hydroxide and ammonia, the alkaline solution may be combined with the third solution in an amount effective to provide a pH greater than or equal to 10, preferably 10-13, more preferably 11-12. In one aspect, particularly when the alkaline solution comprises an alkali metal hydroxide and optional ammonia, at a pH less than 10, no precipitate is produced or separated from the third solution.
[0034] The combination of the alkaline solution and the third solution can be co-precipitated into a purified mixed metal composition (referred to herein as a "precipitate" for simplicity) having a desired ratio of, for example, Ni and Mn. For example, the precipitate can include Ni(OH)2 and Mn(OH)2, preferably included in a molar ratio of greater than 0 to 0.5: greater than 0 to 2, preferably 0.5:1.5. In one aspect, the precipitate can include NiCO3 and MnCO3, preferably included in a molar ratio of greater than 0 to 0.5: greater than 0 to 2, preferably 0.5:1.5. Based on the total weight of the precipitate, the precipitate can further include 5 to 100 ppm of Li, such as 10 to 25 ppm of Li.
[0035] Optionally, a chelating agent may be added to the third solution. The chelating agent may be added to the third solution before, during, or after the addition of the alkaline solution. Exemplary chelating agents may include, but are not limited to, 5-sulfosalicylic acid. When present, the chelating agent may be added to the third solution in an amount effective to provide a concentration of 0.1 to 10 M.
[0036] The method may further include separating the precipitate. Any suitable liquid-solid separation technique may be used for separation, including, for example, filtration, centrifugation, or a combination thereof. The precipitate may be washed (e.g., with deionized water, distilled water, or a combination thereof) and dried (e.g., at a temperature of 80 to 100° C., such as 85 to 95° C., under nitrogen).
[0037] The method further includes adding a lithium compound to the precipitate to form a lithiated precursor mixture (also referred to herein as a "mixture" for simplicity), and heat treating the precursor mixture under conditions effective to provide a cathode active material containing at least one phase having a spinel structure. Exemplary lithium compounds can include lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, or combinations thereof. In one aspect, the lithium compound can include lithium hydroxide.
[0038] Heat treating the mixture can include calcining at a temperature of 550 to 950° C. for 4 to 48 hours in the presence of air. In one aspect, heat treating the mixture can include calcining at a first temperature of 800 to 1000° C. for a first time period in the presence of air, and subsequent to the first time period, calcining at a second temperature of 600 to less than 800° C. for a second time period.
[0039] Thus, the cathode active material may include Li and a metal including Ni and Mn. Li and the metal (ie, Ni and Mn) may be present in a Li:metal ratio of 1:1.67 to 1:2.1, preferably 1:2.
[0040] For example, the cathode active material may comprise a compound according to the formula:
[0041] Li 1+x M 2+y O 4-z A z
[0042] Wherein M is Ni and Mn, A is an oxygen vacancy, F, Cl, or a combination thereof, 0≤x≤0.2, 0≤y≤0.1, and 0≤z≤0.1, and wherein according to the formula Li 1+x M 2+y O 4-z A z The compound has a spinel structure. In one aspect, the cathode active material obtained may include Li 1+x Ni 0.5 Mn 1.5 O4, where 0≤x≤0.2, preferably LiNi 0.5 Mn 1.5 O4. Other cathode active materials may be obtained according to the methods described herein using alternative cell chemistries, alternative composition stoichiometries, or both.
[0043] The cathode active material prepared by the method disclosed herein comprises at least one phase having a spinel structure. As understood by the technicians of solid-state science and as used herein, "spinel structure" refers to the compound being isostructural with spinel, i.e., MgAl2O4. The spinel structure may refer to a phase having a cubic crystal structure comprising MO6 octahedrons (wherein M is Ni and Mn) and a space group of Fd-3m or P4332. The spinel structure of the cathode active material may be characterized using, for example, X-ray diffraction (XRD).
[0044] Cathode active materials prepared according to the methods described herein represent another aspect of the present disclosure.
[0045] In one aspect, the cathode active material may comprise a material having the formula Li 1+x M2+y O 4-z A z and a first phase having a spinel structure, and a second phase, where M is Ni and Mn; A is an oxygen vacancy, F, Cl, or a combination thereof; 0 ≤ x ≤ 0.2; 0 ≤ y ≤ 0.1; 0 ≤ z ≤ 0.1; and the second phase is derived from recycled raw materials. For example, the second phase may include a compound containing one or more of Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof. In one aspect, based on the total weight of the cathode active material, the second phase derived from recycled raw materials is present in an amount of 0.01 to 10 weight percent (wt%), 0.1 to 5 wt%, or 0.2 to 2 wt%. In one aspect, Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof may be derived from recycled raw materials.
[0046] In one aspect, the cathode active material may include a first phase of formula Li 1+x M 2+y O 4-z A z having a spinel structure, where M is Ni and Mn; A is an oxygen vacancy, F, Cl, or a combination thereof; 0 ≤ x ≤ 0.2; 0 ≤ y ≤ 0.1; 0 ≤ z ≤ 0.1; and where the first phase further includes Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof.
[0047] The cathode active material may optionally further include a layered phase. The layered phase is a compound having a layered structure, such as a compound isostructural with LiCoO2. For example, the layered phase may include a layered Li u MO2 phase, where 0 < u < 1.5 and where M is Ni, Co, Mn, Al, or a combination thereof. In one aspect, the layered phase may include a layered LiNi x Co y Mn 1-x-y O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, and x + y = 1. The layered phase may be derived from recycled raw materials or may be an original layered phase (i.e., a phase not prepared using recycled raw materials). In one aspect, the layered phase is derived from recycled raw materials. The layered phase may include one or more of the following: Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof. In one aspect, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof may be derived from recycled raw materials.
[0048] When present, the first phase and the lamellar phase can be present in the cathode active material in a weight ratio of 1:99 to 99:1, or 10:90 to 90:10, or 20:80 to 80:20, or 30:70 to 70:30, or 40:60 to 60:40, or 45:55 to 55:45.
[0049] In one aspect, the cathode active material can be used in combination with a native cathode active material (i.e., not prepared using recycled raw materials). For example, the cathode active material can include: a first cathode active material, the first cathode active material including a spinel structure of formula Li 1+x M 2+y O 4-z A z A first phase derived from a recycled raw material; and a second phase derived from a recycled raw material; and a second cathode active material containing a cathode active material derived from a virgin raw material. In one aspect, the cathode active material may include: a first cathode active material comprising a first phase and further comprising Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof; and a second cathode active material containing a cathode active material derived from a virgin raw material. The cathode active material of the present disclosure and the virgin cathode active material may be combined in a weight ratio of 1:99 to 99:1, or 10:90 to 90:10, or 20:80 to 80:20, or 30:70 to 70:30, or 40:60 to 60:40, or 45:55 to 55:45, or 50:50.
[0050] The cathode active materials disclosed herein may exhibit one or more advantageous properties. For example, when using a lithium anode and an electrolyte containing 1MLiPF6 in a 1:1 ratio by volume of ethylene carbonate: dimethyl carbonate, the cathode active material may have a discharge capacity of greater than 100mAh / g (e.g., 135mAh / g) at a discharge rate of C / 20 for a half-cell at 20°C after 100 cycles. In one aspect, the cathode active material may have a discharge capacity of 110mAh / g at a rate of 5C or a discharge capacity of 90mAh / g at a rate of 10C after 100 cycles. The C rate refers to the current discharged by the battery in one hour, so 10C refers to the current discharged by the battery in 6 minutes.
[0051] The cathode active materials described herein are particularly useful in battery cathodes. Thus, a battery cathode can include a cathode active material made by the methods described herein, optionally in combination with a virgin cathode active material (ie, a material not prepared using recycled feedstock).
[0052] The following non-limiting examples further illustrate the present disclosure.
[0053] Example
[0054] Comparative Example 1
[0055] A metal sulfate aqueous solution (MSO4) was prepared using battery - grade starting materials, having a concentration of 2 moles per liter (M) and a Ni:Mn stoichiometric ratio of 1:3. Ethanol was added to the metal sulfate solution at a concentration of 10 weight percent based on the total weight of the solution.
[0056] NH4HCO3 or (NH4)2CO3 was used as a precipitant. A 0.15 M solution of NH4HCO3 or (NH4)2CO3 was added to a 3 - liter (L) continuously stirred tank reactor (CSTR), and then the metal sulfate solution (MSO4) was co - added to form a precipitate. The precipitate slurry was stirred at a temperature of 25 to 80 °C for 3 to 24 hours.
[0057] The precipitate was filtered and washed with water. To ensure the removal of any residual sulfate ions or metal impurity ions on the surface of the precipitate, the conductivity of the filtrate solution was monitored until it was far below 400 μS / cm. Then the filtered wet cake was dried under a N2 stream at 90 °C to provide a precursor cathode active material (pCAM).
[0058] The cathode active material (CAM) was prepared from the pCAM of Comparative Example 1 by mixing the crushed pCAM with a lithium source (e.g., LiOH, Li2CO3, Li2C2O4) at a Li:M molar ratio of 0.5 < Li:M < 0.6. The mixture was calcined in air at a temperature of 850 °C for 24 hours and then at 600 °C for 10 hours. After cooling, the CAM was crushed and screened using a 350 - mesh sieve. Analysis by ICP - OES showed Ni:Mn to be 1:3. Analysis by X - ray diffraction (XRD) showed the obtained spinel crystal structure.
[0059] Example 1
[0060] A metal sulfate aqueous solution (MSO4) having a concentration of 2 moles per liter (M) and a Ni:Mn stoichiometric ratio of 1:3 was prepared using 30 wt% recycled mixed metal sulfate and 70 wt% battery - grade starting materials (i.e., NiSO4 and MnSO4). The recycled mixed metal sulfate (MMS) contained 20 wt% Ni and 0.86 wt% Co and trace impurities (e.g., Al, Cu). Ethanol was added to the metal sulfate solution at a concentration of 10 weight percent based on the total weight of the solution.
[0061] Use NH4HCO3 or (NH4)2CO3 as a precipitating agent. Add 0.15 moles (M) of an NH4HCO3 or (NH4)2CO3 solution to a 3-liter (L) continuously stirred tank reactor (CSTR), and then add a metal sulfate solution (MSO4) in total to form a precipitate. Stir the precipitate slurry at a temperature of 25 to 80 °C for 3 to 24 hours.
[0062] Filter the precipitate and wash it with water. To ensure the removal of any residual sulfate ions or metal impurity ions on the surface of the precipitate, monitor the conductivity of the filtrate solution until it is much lower than 400 μS / cm. Then dry the filtered wet cake at 90 °C under a stream of N2 to provide a precursor cathode active material (pCAM).
[0063] The cathode active material (CAM) is prepared from the pCAM of Example 1 by mixing the crushed pCAM with a lithium source (e.g., LiOH, Li2CO3, Li2C2O4) at a Li:M molar ratio of 0.5 < Li:M < 0.6. Calcinate the mixture in air at a temperature of 850 °C for 24 hours, and then calcinate it at 600 °C for 10 hours. After cooling, crush the CAM and screen it using a 350-mesh sieve. Analysis by ICP-OES shows Ni:Mn to be 1:3. Analysis by X-ray diffraction (XRD) shows the obtained spinel crystal structure.
[0064] Example 2
[0065] The cathode active material is prepared using the same materials and steps as in Example 1, except that diethylene glycol is used as a co-solvent to replace ethanol during the precipitation process.
[0066] The present disclosure further includes the following aspects.
[0067] Aspect 1: A method of manufacturing a cathode active material, the method comprising: contacting a mixed metal composition with water to form a first solution, the mixed metal composition comprising nickel and a compound containing Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof in an amount greater than 0 to 2 weight percent based on the total weight of the mixed metal composition; adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution; adding a co-solvent to the second solution to provide a third solution; combining the third solution and an alkaline solution to form a precipitate; adding a lithium compound to the precipitate to form a mixture; and subjecting the mixture to a heat treatment under conditions effective to provide the cathode active material, wherein the cathode active material comprises at least one phase having a spinel structure.
[0068] Aspect 2: A method for manufacturing a cathode active material, the method comprising: contacting a mixed metal composition with water to form a first solution, the mixed metal composition comprising nickel and manganese, and a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof in an amount greater than 0 to 2 weight percent based on the total weight of the mixed metal composition; adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution; adding a co-solvent to the second solution to provide a third solution; combining the third solution and an alkaline solution to form a precipitate; adding a lithium compound to the precipitate to form a mixture; and heat treating the mixture under conditions effective to provide a cathode active material; wherein the cathode active material comprises at least one phase having a spinel structure.
[0069] Aspect 3: A method for manufacturing a cathode active material, the method comprising: contacting a mixed metal composition with water to form a first solution, the mixed metal composition comprising manganese, and a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof in an amount greater than 0 to 2 weight percent based on the total weight of the mixed metal composition; adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution; adding a co-solvent to the second solution to provide a third solution; combining the third solution and an alkaline solution to form a precipitate; adding a lithium compound to the precipitate to form a mixture; and heat treating the mixture under conditions effective to provide a cathode active material, wherein the cathode active material comprises at least one phase having a spinel structure.
[0070] Aspect 4: The method according to any one of aspects 1 to 3, wherein the co-solvent comprises C 1-8 Alcohol, C 1-8 Alkylene glycol, C 1-8 Alkylene triols, or combinations thereof, preferably wherein the co-solvent comprises ethanol, isopropanol, ethylene glycol, diethylene glycol, or combinations thereof.
[0071] Aspect 5: The method according to any one of aspects 1 to 4, wherein the co-solvent is present in the third solution in an amount of 1 to 50 weight percent, preferably 5 to 15 weight percent, based on the total weight of the third solution.
[0072] Aspect 6: A method according to any one of aspects 1 or 4 to 5, wherein the mixed metal composition is obtained by a method comprising: contacting electrode particles comprising nickel and greater than 0 to 2 weight percent of a compound containing Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Li, or a combination thereof based on the total weight of the mixed metal composition with a leaching solution (preferably containing sulfuric acid); precipitating the mixed metal composition from the leaching solution; and separating the mixed metal composition from the leaching solution.
[0073] Aspect 7: A method according to any one of Aspects 2 or 4 to 5, wherein the mixed metal composition is obtained by a method comprising: contacting electrode particles comprising nickel and manganese and greater than 0 to 2 weight percent of a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Li, or a combination thereof based on the total weight of the mixed metal composition with a leaching solution (preferably containing sulfuric acid); precipitating the mixed metal composition from the leaching solution; and separating the mixed metal composition from the leaching solution.
[0074] Aspect 8: A method according to any one of Aspects 3 to 5, wherein the mixed metal composition is obtained by a method comprising: contacting electrode particles comprising manganese and greater than 0 to 2 weight percent of a compound containing Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Li, or a combination thereof based on the total weight of the mixed metal composition with a leaching solution (preferably containing sulfuric acid); precipitating the mixed metal composition from the leaching solution; and separating the mixed metal composition from the leaching solution.
[0075] Aspect 9: The method according to any one of aspects 1 to 8, wherein the mixed metal composition comprises mixed metal sulfates, mixed metal nitrates, mixed metal carbonates, mixed metal halides, mixed metal hydroxides, mixed metal oxalates, or combinations thereof.
[0076] Aspect 10: The method according to any one of aspects 1 to 9, wherein the mixed metal composition comprises mixed metal sulfates.
[0077] Aspect 11: The method according to any one of aspects 1 to 10, wherein the mixed metal composition further comprises lithium, preferably in an amount of 100 to 1000 ppm based on the total weight of the mixed metal composition.
[0078] Aspect 12: The method according to any one of aspects 1 to 11, wherein the mixed metal composition is obtained from recycled raw materials, preferably from post-industrial recycled raw materials, post-consumer recycled raw materials, or a combination thereof.
[0079] Aspect 13: A method according to any one of Aspects 1 to 12, wherein the mixed metal composition comprises 0.5 to 1.5 weight percent Co, 50 to 300 ppm Cu, 50 to 200 ppm Al, 5 to 100 ppm Fe, and 5 to 100 ppm F, each based on the total weight of the mixed metal composition.
[0080] Aspect 14: The method according to any one of aspects 1 to 13, wherein the first solution has a pH of less than 7, or less than 6.5.
[0081] Aspect 15: The method according to any one of aspects 1 to 14, wherein the nickel salt, manganese salt, or a combination thereof is a sulfate or hydroxide thereof.
[0082] Aspect 16: The method according to any one of aspects 1 to 15, wherein the method comprises adding a nickel salt or a manganese salt to the first solution in an amount effective to provide a molar ratio of Ni:Mn of greater than 0 to 0.5:greater than 0 to 2, preferably 0.5:1.5.
[0083] Aspect 17: The method according to Aspect 16, wherein the salt comprises NiSO4 and MnSO4.
[0084] Aspect 18: The method according to any one of aspects 1 to 17, wherein the second solution has a pH of less than 7, or less than 6.5.
[0085] Aspect 19: The method according to any one of aspects 1 or 4 to 18, wherein the second solution comprises 0.0001 to 2 weight percent of Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Li, or a combination thereof based on the total weight of the solution.
[0086] Aspect 20: The method according to any one of aspects 2 or 4 to 18, wherein the second solution comprises 0.0001 to 2 weight percent of Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Li, or a combination thereof based on the total weight of the solution.
[0087] Aspect 21: The method according to any one of aspects 3 to 18, wherein the second solution comprises 0.0001 to 2 weight percent of Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Li, or a combination thereof based on the total weight of the solution.
[0088] Aspect 22: The method according to any one of aspects 1 to 21, wherein the alkaline solution comprises a base comprising an alkali metal hydroxide, ammonia, an alkali metal carbonate, an alkali metal bicarbonate, or a combination thereof.
[0089] Aspect 23: A method according to aspect 22, wherein the alkaline solution comprises a base comprising an alkali metal carbonate, an alkali metal bicarbonate, or a combination thereof, preferably wherein the alkali metal carbonate and the alkali metal bicarbonate are present in a ratio of 1.04:1 to 1:1.04, preferably 1.01:1 to 1:1.01, and more preferably 1:1.
[0090] Aspect 24: The method according to aspect 23, wherein the alkaline solution is combined with the third solution in an amount effective to provide a pH greater than 7, preferably 7 to 10, or 7 to 9, or 7 to 8.
[0091] Aspect 25: The method according to aspect 22, wherein the alkaline solution comprises an alkali metal hydroxide, preferably sodium hydroxide and ammonia, more preferably wherein the sodium hydroxide and ammonia are present in a ratio of 1.04:1 to 1:1.04, preferably 1.01:1 to 1:1.01, more preferably 1:1.
[0092] Aspect 26: The method according to aspect 25, wherein the alkaline solution is combined with the third solution in an amount effective to provide a pH greater than or equal to 10, preferably 10-13, more preferably 11-12.
[0093] Aspect 27: The method according to any one of aspects 1 to 26, further comprising adding a chelating agent to the third solution, preferably wherein the chelating agent is present in an amount of 0.1 to 10 M in the third solution.
[0094] Aspect 28: The method according to aspect 23 or 24, wherein the precipitate preferably comprises NiCO3 and MnCO3 in a molar ratio of greater than 0 to 0.5: greater than 0 to 2, preferably 0.5:1.5.
[0095] Aspect 29: The method according to aspect 25 or 26, wherein the precipitate preferably comprises Ni(OH)2 and Mn(OH)2 in a molar ratio of greater than 0 to 0.5: greater than 0 to 2, preferably 0.5:1.5.
[0096] Aspect 30: The method according to any one of aspects 1 to 29, wherein the precipitate comprises 5 to 100 ppm Li, preferably 10 to 25 ppm Li, based on the total weight of the precipitate.
[0097] Aspect 31: The method according to any one of aspects 1 to 30, wherein the lithium compound comprises lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, or a combination thereof.
[0098] Aspect 32: The method according to any one of aspects 1 to 31, wherein the cathode active material comprises Li at a Li:metal ratio of 1:1.9 to 1:2.1, or 1:2 to 1:2.1.
[0099] Aspect 33: The method according to any one of aspects 1 to 32, wherein the heat treatment comprises calcining at a temperature of 550 to 950° C. for 4 to 48 hours in the presence of air.
[0100] Aspect 34: The method according to any one of aspects 1 to 33, wherein the heat treatment comprises calcining at a first temperature of 800 to 1000°C for a first time in the presence of air, and after the first time, calcining at a second temperature of 600 to less than 800°C for a second time.
[0101] Aspect 35: The method according to any one of aspects 1 to 34, further comprising stirring the third solution at a temperature of 25 to 90°C and a speed of 500 to 1500 RPM.
[0102] Aspect 36: The method according to any one of aspects 1 to 35, further comprising isolating the precipitate.
[0103] Aspect 37: A cathode active material produced by the method of any one of aspects 1 to 36.
[0104] Aspect 38: A cathode active material comprising: having a formula Li 1+x M 2+y O 4-z A z and a first phase having a spinel structure; and a second phase; wherein M is Ni and Mn; A is an oxygen vacancy, F, Cl, or a combination thereof; 0≤x≤0.2; 0≤y≤0.1; 0≤z≤0.1; and the second phase is derived from recycled raw materials.
[0105] Aspect 39: The cathode active material according to aspect 38, wherein the second phase comprises one or more of Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, or Li.
[0106] Aspect 40: The cathode active material according to aspect 38 or 39, wherein the second phase derived from the recycled feedstock is present in an amount of 1 to 99 weight percent based on the total weight of the cathode active material.
[0107] Aspect 41: A cathode active material comprising: having a formula Li 1+x M 2+y O 4-z A z And a first phase having a spinel structure, wherein M is Ni and Mn, A is oxygen vacancy, F, Cl, or a combination thereof, 0≤x≤0.2, 0≤y≤0.1, 0≤z≤0.1, and wherein the first phase further contains Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof.
[0108] Aspect 42: The cathode active material according to aspect 41, wherein Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof is derived from recycled raw materials.
[0109] Aspect 43: A cathode active material according to any one of aspects 38 to 42, wherein the first phase comprises LiNi 0.5 Mn 1.5 O4.
[0110] Aspect 44: The cathode active material according to any one of Aspects 38 to 43 further comprises a layered phase, which is preferably isostructural with LiCoO2.
[0111] Aspect 45: The cathode active material according to Aspect 44, wherein the layered phase comprises a layered phase having the formula Li u MO2, where 0 < u < 1.5 and where M is Ni, Co, Mn, Al, or a combination thereof.
[0112] Aspect 46: The cathode active material according to Aspect 44 or 45, wherein the layered phase comprises layered LiNi x Co y Mn 1-x-y O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, and x + y = 1.
[0113] Aspect 47: The cathode active material according to any one of Aspects 44 to 46, wherein the layered phase is derived from recycled raw materials.
[0114] Aspect 48: The cathode active material according to Aspect 47, wherein the layered phase comprises one or more of Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof.
[0115] Aspect 49: The cathode active material according to Aspect 47 or 48, wherein the layered phase further comprises Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof.
[0116] Aspect 50: The cathode active material according to Aspect 49, wherein Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof is derived from recycled raw materials.
[0117] Aspect 51: The cathode active material according to any one of Aspects 44 to 50, wherein the first phase and the layered phase are present in a weight ratio of 1:99 to 99:1, or 10:90 to 90:10, or 20:80 to 80:20, or 30:70 to 70:30, or 40:60 to 60:40, or 45:55 to 55:45.
[0118] Aspect 52: The cathode active material according to Aspect 38, comprising a first cathode active material (comprising a first phase; and a second phase derived from recycled raw materials); and a second cathode active material (comprising a cathode active material derived from virgin feedstock).
[0119] Aspect 53: A cathode active material according to Aspect 41, comprising a first cathode active material (comprising a first phase and further comprising Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof); and a second cathode active material (comprising a cathode active material derived from a native raw material).
[0120] Aspect 54: The cathode active material according to aspect 52 or 53, wherein the first cathode active material and the second cathode active material are combined in a weight ratio of 1:99 to 99:1.
[0121] The compositions and methods may alternatively comprise, consist of, or consist essentially of any suitable material, step, or component disclosed herein. The compositions and methods may also or alternatively be configured to be free of, or substantially free of, any material (or species), step, or component that is otherwise unnecessary for achieving the function or purpose of the compositions, methods, and articles.
[0122] All ranges disclosed herein include endpoints, and these endpoints can be combined independently of each other. "Combination" includes blends, mixtures, alloys, reaction products, etc. The terms "first", "second", etc. do not represent any order, quantity or importance, but are used to distinguish one element from another element. The terms "one", "an" and "the" do not represent quantitative restrictions, and should be understood to cover singular and plural numbers, unless otherwise specified herein or the context is obviously contradictory. "Or" means "and / or", unless otherwise explicitly stated. Mentioning "aspects" throughout the specification means that the specific elements described in connection with the aspect are included in at least one aspect described herein, and may or may not be present in other aspects. The term "their combination" used herein includes one or more of the listed elements, and is open, allowing one or more unmentioned similar elements to exist. In addition, it should be understood that the described elements can be combined in any suitable manner in various aspects.
[0123] It should also be understood that when used in this specification, the terms “comprises” and / or “comprising”, or “includes” or “including” refer to the presence of stated features, regions, integers, steps, operations, elements or components, but do not exclude the presence or addition of one or more other features, regions, integers, steps, operations, elements, components or groups thereof.
[0124] Various aspects are shown in the accompanying drawings. However, the present invention can be embodied in many different forms and should not be construed as limited to the aspects set forth herein. On the contrary, these aspects are provided to make this disclosure comprehensive and complete and to fully convey the scope of the present invention to those skilled in the art. Throughout the document, the same reference numerals refer to the same elements.
[0125] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present disclosure belongs. It should be further understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technical field and the present disclosure, and will not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.
[0126] U.S. Provisional Patent Application No. 63 / 338,485, filed on May 5, 2022, is hereby incorporated by reference in its entirety for all purposes.
[0127] While certain aspects have been described, there are alternatives, modifications, variations, improvements, and substantial equivalents that are not currently foreseen or may not be foreseen that may occur to the applicant or others skilled in the art. Accordingly, the appended claims as filed and as they may be amended are intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.
Claims
1. A method for producing a cathode active material, the method comprising: contacting a mixed metal composition with water to form a first solution, the mixed metal composition comprising: Nickel, and greater than 0 to 2 weight percent of a compound comprising Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or combinations thereof, based on the total weight of the mixed-metal composition; adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution; adding a co-solvent to the second solution to provide a third solution; combining the third solution and the alkaline solution to form a precipitate; adding a lithium compound to the precipitate to form a mixture; as well as thermally treating the mixture under conditions effective to provide the cathode active material, The cathode active material comprises at least one phase having a spinel structure.
2. A method for producing a cathode active material, the method comprising: contacting a mixed metal composition with water to form a first solution, the mixed metal composition comprising: Nickel and manganese, and greater than 0 to 2 weight percent of a compound comprising Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed-metal composition; adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution; adding a co-solvent to the second solution to provide a third solution; combining the third solution and the alkaline solution to form a precipitate; adding a lithium compound to the precipitate to form a mixture; as well as thermally treating the mixture under conditions effective to provide the cathode active material; The cathode active material comprises at least one phase having a spinel structure.
3. A method for producing a cathode active material, the method comprising: contacting a mixed metal composition with water to form a first solution, the mixed metal composition comprising: Manganese, and greater than 0 to 2 weight percent of a compound comprising Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof, based on the total weight of the mixed-metal composition; adding a nickel salt, a manganese salt, or a combination thereof to the first solution to provide a second solution; adding a co-solvent to the second solution to provide a third solution; combining the third solution and the alkaline solution to form a precipitate; adding a lithium compound to the precipitate to form a mixture; as well as thermally treating the mixture under conditions effective to provide the cathode active material, The cathode active material comprises at least one phase having a spinel structure.
4. The method according to claim 1, wherein the co-solvent comprises C 1-8 Alcohol, C 1-8 Alkylene glycol, C 1-8 Alkylene triol, or a combination thereof; Optionally, the co-solvent is present in the third solution in an amount of 1 to 50 weight percent based on the total weight of the third solution.
5. The method of claim 1, wherein the mixed metal composition is obtained by a process comprising: contacting electrode particles with a leaching solution; the electrode particles comprising: Nickel, and greater than 0 to 2 weight percent of a compound comprising Co, Mn, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Li, or combinations thereof, based on the total weight of the mixed-metal composition; precipitating the mixed metal composition from the leaching solution; and The mixed metal mixture is separated from the leaching solution.
6. The method of claim 2, wherein the mixed metal composition is obtained by a process comprising: contacting electrode particles with a leaching solution; the electrode particles comprising: Nickel and manganese, and greater than 0 to 2 weight percent of a compound comprising Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Li, or a combination thereof, based on the total weight of the mixed-metal composition; precipitating the mixed metal composition from the leaching solution; and The mixed metal mixture is separated from the leaching solution.
7. The method of claim 3, wherein the mixed metal composition is obtained by a process comprising: contacting electrode particles with a leaching solution; the electrode particles comprising: Manganese, and greater than 0 to 2 weight percent of a compound comprising Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Li, or a combination thereof, based on the total weight of the mixed-metal composition; precipitating the mixed metal composition from the leaching solution; and The mixed metal mixture is separated from the leaching solution.
8. The method of claim 1, wherein the mixed metal composition comprises mixed metal sulfates, mixed metal nitrates, mixed metal carbonates, mixed metal halides, mixed metal hydroxides, mixed metal oxalates, or combinations thereof.
9. The method of claim 1, wherein the mixed metal composition further comprises lithium.
10. The method of claim 1, wherein at least a portion of the mixed metal composition is obtained from recycled feedstock.
11. The method of claim 1, wherein the first solution has a pH of less than 7 or wherein the second solution has a pH of less than 7.
12. The method of claim 1, wherein the nickel salt, manganese salt, or a combination thereof is a sulfate or hydroxide thereof.
13. The method of claim 1, wherein the method comprises adding a nickel salt or a manganese salt to the first solution in an amount effective to provide a Ni:Mn molar ratio of greater than 0 to 0.5: greater than 0 to 2.
14. The method of claim 1, wherein the alkaline solution is combined with the third solution in an amount effective to provide a pH greater than 7.
15. The method of claim 1, wherein the alkaline solution is combined with the third solution in an amount effective to provide a pH greater than or equal to 10.
16. The method of claim 1, wherein the precipitate comprises NiCO3 and MnCO3.
17. The method of claim 1, wherein the precipitate comprises Ni(OH)2 and Mn(OH)2.
18. The method of claim 1, wherein the precipitate comprises 5 to 100 ppm of Li based on the total weight of the precipitate.
19. The method of claim 1, wherein the lithium compound comprises lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, or a combination thereof.
20. The method of claim 1, wherein the cathode active material comprises Li at a Li:metal ratio of 1:1.9 to 1:2.
1.
21. A cathode active material produced by the method of any one of claims 1 to 20.
22. A cathode active material comprising: The first phase, with the formula Li 1+x M 2+y O 4-z A z and having a spinel structure; and Phase II; in, M is Ni and Mn; A is an oxygen vacancy, F, Cl, or a combination thereof; 0≤x≤0.2; 0≤y≤0.1; 0≤z≤0.1; and The second phase originates from the recycled feedstock.
23. The cathode active material according to claim 22, wherein the second phase comprises one or more of Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, or Li.
24. A cathode active material, comprising: A first phase having the formula Li 1+x M 2+y O 4-z A z and having a spinel structure; wherein, M is Ni and Mn, A is an oxygen vacancy, F, Cl, or a combination thereof, 0≤x≤0.2, 0≤y≤0.1, 0≤z≤0.1, and The first phase further comprises Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof.
25. The cathode active material according to claim 24, wherein Co, Al, Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof is derived from recycled raw materials.
26. The cathode active material according to any one of claims 22 to 25, further comprising a layered phase.
27. The cathode active material according to claim 26, wherein the layered phase comprises a layered phase having the formula Li u MO2, where 0 < u < 1.5 and where M is Ni, Co, Mn, Al, or a combination thereof.
28. The cathode active material according to claim 26, wherein the layered phase comprises layered LiNi x Co y Mn 1-x-y O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, and x + y = 1.
29. The cathode active material according to claim 26, wherein the layered phase is derived from recycled raw materials.
30. The cathode active material according to claim 29, wherein the layered phase comprises one or more of Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof.
31. The cathode active material according to claim 29, wherein the layered phase further comprises Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof.
32. The cathode active material of claim 31, wherein the Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof is derived from recycled feedstock.
33. The cathode active material of claim 22, comprising: a first cathode active material comprising the first phase and the second phase derived from a recycled feedstock; and The second cathode active material comprises a cathode active material derived from a virgin raw material.
34. The cathode active material of claim 24, comprising: a first cathode active material comprising a first phase and further comprising Cu, Fe, Mg, Na, Ca, Zn, F, Si, Li, or a combination thereof; and The second cathode active material comprises a cathode active material derived from a virgin raw material.
35. The cathode active material of claim 33 or 34, wherein the first cathode active material and the second cathode active material are combined in a weight ratio of 1:99 to 99:1.
